2013
DOI: 10.1021/jf400275m
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Controlled Uptake and Release of Anthocyanins by Oxidized Starch Microgels

Abstract: Anthocyanins are well-known antioxidants, but they are sensitive to environmental conditions. Herein we used oxidized starch microgel to prevent their early degradation and deliver them to the target place. The aim of this study was to investigate the uptake and the release ability of anthocyanins by the oxidized starch microgels and measure their in vitro gastrointestinal release. The gels were made of oxidized potato starch polymers, which were chemically cross-linked by sodium trimetaphosphate (STMP). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…As shown in Figure 7, the asymmetric vibration ν as of COO − in the OKGM polymer appears at 1608.4 cm −1 , but this peak is split into two peaks at 1737. 6 3) cm −1 , suggesting the coexistence of unidentate binding (Δν as-s ≫ 200 cm −1 ) and bridging (Δν as-s ≈ 200 cm −1 ) between COO − and Fe 3+ in the OKGM particle. Two coordination modes between Fe 3+ and COO − are consistent with the results from Mossbauer spectroscopy (Figure 6), where it was observed that the ratio between the two different modes is about 1:2.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…As shown in Figure 7, the asymmetric vibration ν as of COO − in the OKGM polymer appears at 1608.4 cm −1 , but this peak is split into two peaks at 1737. 6 3) cm −1 , suggesting the coexistence of unidentate binding (Δν as-s ≫ 200 cm −1 ) and bridging (Δν as-s ≈ 200 cm −1 ) between COO − and Fe 3+ in the OKGM particle. Two coordination modes between Fe 3+ and COO − are consistent with the results from Mossbauer spectroscopy (Figure 6), where it was observed that the ratio between the two different modes is about 1:2.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The anthocyanins content in extract powder was measured by pH differential method (Wang, Li, Chen, Xin, & Yuan, 2013) using a UV-Vis spectrophotometry (Agilent CARY 100, Varian Corporation, USA). The anthocyanins extract powder (20 mg) was dissolved in 10 mL distilled water, and 1 mL anthocyanins solution was dissolved in 9 mL of 0.025 M potassium chloride buffer (pH 1.0) and 9 mL of 0.4 M sodium acetate buffer (pH 4.5) respectively in separate test tubes.…”
Section: Determination Of Total Anthocyanins Content In Extract Powdermentioning
confidence: 99%
“…The anthocyanins content in lyophilized RRA extract powder was measured by the pH differential method. 35 Absorbance of sample at 520 and 700 nm was measured using a UV-Vis spectrophotometry (Agilent CARY 100, Varian Corporation, USA). The anthocyanin content was expressed in mg/g.…”
Section: Materials and Reagentsmentioning
confidence: 99%